Evaluation of Drug use Pattern and Behavior in Rural and Urban Population - Rama, P; Jose, Eldhose; Paul, Jisni M; R, Keerthana; Raghava V, Geetha (Indian Journal of Pharmacy Practice)
Background: Irrational use of medicines leads to problems such as ineffective treatment, health risks non-adherence, medication wastages, needless expenditure, improper storage and disposal of medicine. Self-medication and health care seeking behaviour pattern varies among different populations. Aim: The study aimed to evaluate the drug use pattern and behaviour in urban and rural population on behalf of their medication usage. Materials and Methods: A cross-sectional study was conducted with a validated questionnaire among 300 participants excluding healthcare professionals, 150 each from urban and rural areas of Coimbatore district, Tamil Nadu. Results: From the study we observed that 61.3% in urban and 58% in rural population had the habit of checking expiry date before using their medication. 80% and 57% of the participants carried their previous prescriptions during doctor visit in rural and urban community respectively. 3.3% of participants had the habit of suggesting and lending their medicines. 27.3% of rural and 14.6% of urban participants repurchased medicines with their previous prescriptions. 40.3% of participants were consulting pharmacists for drug information. Majority of our participants from both communities had a habit of disposing their unused or expired medications in trash. The prevalence of self-medication was 86.6% and 67.2% in urban and rural populations respectively. Conclusion: From the study we conclude that both the communities have imperfections with drug use practice such as Adherence, self-medication, drug disposal and repurchase of medications. This suggests the strong need for implementation of population need-based awareness programs in both the communities.
Keywords: Self-medication; Adherence; Drug Disposal; Medicine Sharing; Drug use practice; Urban and Rural.